THE ROLE OF EMPLOYEE MOTIVATION - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
THE ROLE OF EMPLOYEE MOTIVATION is the most important thing for any public or private sector organizations. This is supported by the statement that motivation plays an important role in the success of any organization either in the public or private sector (Chintalloo and Mahadeo, 2013).Based on the theory and the hypothesis proposed in this study are: employee motivation is affected service quality positively; employee competence gives positive effect on service quality; employee motivation delivers a positive influence on employee performance; employee competence positively affected employee performance; service quality has a positive impact on employee performance.